Gasification biochar has limited effects on functional and structural diversity of soil microbial communities in a temperate agroecosystem. (August 2016) - Imparato, Valentina; Hansen, Veronika; Santos, Susana S.; Nielsen, Tue Kjærgaard; Giagnoni, Laura; Hauggaard-Nielsen, Henrik; Johansen, Anders; Renella, Giancarlo; Winding, Anne
Abstract: Biochar may enhance soil fertility and carbon (C) sequestration but there is still a lack of comprehensive understanding of its effects on soil microbial communities and functioning. This study tested the differential effects of two doses (6–8 and 0.8–1.4 t ha −1 for High and Low doses, respectively) of wheat straw gasification biochar (GBC) and fresh straw incorporated as soil amendments into an agricultural field in Denmark. Soils were analysed three months after the amendments for pH, total organic matter, microbial biomass (ATP), ten enzymatic activities, catabolic potential by substrate-induced respiration (MicroResp™), soil toxicity test (BioTox™) and bacterial community structure (Illumina 16S rRNA gene sequencing). No significant effect of biochar treatment was observed regarding ATP content, catabolic community profiles and soil toxicity. The higher dose of GBC increased phenol oxidase activity and soil pH, and decreased the cellulase activity. No major effect of high dose GBC was observed on the soil community diversity, and only minor effect on the community composition, with an increase in the relative abundance of a single OTU associated with Acidobacteria_Gp16 . Addition of low dose of GBC caused an increase in the relative abundance of the rare members in the microbial communities thus increasing the diversity of soil microorganisms. A comparable effect was observed with the addition of fresh straw. Overall, our results indicated that GBC as soil amendment had a limited effect on the functional and structural diversity of soil microbial communities in a Danish temperate agroecosystem. Graphical abstract: Highlights: Application of high dose of biochar increased phenol oxidase activity. Application of high dose of biochar reduced cellulase activity. Application of biochar did not alter potential soil catabolic response profile. Two doses of biochar altered microbial diversity differently. Low dose of biochar enhanced the abundance of low abundance taxa.